2022
DOI: 10.3390/cells11071213
|View full text |Cite
|
Sign up to set email alerts
|

5-Azacytidine Inhibits the Activation of Senescence Program and Promotes Cytotoxic Autophagy during Trdmt1-Mediated Oxidative Stress Response in Insulinoma β-TC-6 Cells

Abstract: 5-Azacytidine (5-azaC), a methyltransferase inhibitor and anticancer drug, can promote several cellular stress responses such as apoptosis, autophagy, and senescence. The action of 5-azaC is complex and can be modulated by dose, time of treatment, and co-administration with oxidants. Insulinoma is a rare pancreatic neuroendocrine tumor with limited chemotherapeutic options. In the present study, two cellular models of insulinoma were considered, namely NIT-1 and β-TC-6 mouse cells, to evaluate the effects of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
1
5
0
1
Order By: Relevance
“…Conversely, our results indicate that the treatment with 5-azacytidine, inducing tuberin expression, reduced the senescent features of LAM/TSC cells, which decrease the positivity to SA-β galactosidase. These data are consistent with the recent study in which 24 h of incubation with 5-azacytidine inhibited senescence in insulinoma cell lines established from transgenic mice [37]. In this case, the drug treatment caused cytotoxicity, which was not observed in our experimental conditions.…”
Section: Discussionsupporting
confidence: 94%
“…Conversely, our results indicate that the treatment with 5-azacytidine, inducing tuberin expression, reduced the senescent features of LAM/TSC cells, which decrease the positivity to SA-β galactosidase. These data are consistent with the recent study in which 24 h of incubation with 5-azacytidine inhibited senescence in insulinoma cell lines established from transgenic mice [37]. In this case, the drug treatment caused cytotoxicity, which was not observed in our experimental conditions.…”
Section: Discussionsupporting
confidence: 94%
“…2). We have previously shown that 5-azacytidine, a methyltransferase inhibitor, provoked eIF2α-based response in oxidant-stressed mouse insulinoma β-TC-6 cells that was mediated by elevated levels of Trdmt1 [60]. However, 5-azacytidine treatment resulted in functional inactivation of Trdmt1 and cell elimination by the means of cytotoxic autophagy [60].…”
Section: Dnmt2/trdmt1 Gene Knockout Suppresses Dox-mediated Activatio...mentioning
confidence: 97%
“…We have previously shown that 5-azacytidine, a methyltransferase inhibitor, provoked eIF2α-based response in oxidant-stressed mouse insulinoma β-TC-6 cells that was mediated by elevated levels of Trdmt1 [60]. However, 5-azacytidine treatment resulted in functional inactivation of Trdmt1 and cell elimination by the means of cytotoxic autophagy [60]. In the present study, DNMT2/ TRDMT1 gene knockout also affected DOX-induced UPR signaling and ER stress leading to apoptotic cell death when cancer cells were incubated with ER stress inducer for 48 h (Fig.…”
Section: Dnmt2/trdmt1 Gene Knockout Suppresses Dox-mediated Activatio...mentioning
confidence: 99%
“…This demethylation also contributes to the restoration of myogenic regulatory factors (MRFs) such as MyoD and myogenin, which are crucial for myogenic differentiation [ 58 ]. Furthermore, 5-Azacytidine can induce cell cycle arrest and cellular senescence, promoting a more mature cellular state in ARMS [ 59 ]. However, it is important to note that 5-Azacytidine’s effectiveness often varies among patients and is often used in the context of personalized treatment plans for ARMS, typically under clinical trial conditions.…”
Section: Arms Chemotherapy Drugs and Their Impact On Tumor Cell Diffe...mentioning
confidence: 99%